Field investigation of ultra-high performance concrete shear key in an adjacent box-girder bridge. Issue 5 (4th May 2019) - Hussein, Husam H.; Sargand, Shad M.; Khoury, Issam
Abstract: Adjacent box girders are widely used in short to intermediate span bridges in several states because they make bridges quick and easy to build. However, the strength and serviceability of this type of bridge can frequently be compromised by the reductions in efficiency of load transfer and shear resistance due to joint degradation at the shear keys. Because of its superior mechanical properties and improved durability, ultra-high performance concrete (UHPC) has been proposed as an alternative grout material to eliminate shear key degradation. In this project, a single-span adjacent box-girder bridge was instrumented and monitored to investigate the performance of the UHPC shear keys under truck loads. The parameters of primary importance to shear key performance were identified from the response data. A finite element (FE) model of the bridge was developed to evaluate the efficiency of the load transfer mechanism at the UHPC joints. The UHPC shear key and transverse shear reinforcement bars fully transferred the load through the joints due to high bond strength of UHPC. The maximum relative displacement for all load cases was 0.151 mm (0.00594 in.) insufficient to cause damage to the UHPC shear key interface.